Health-related quality of life of children and adolescents with type 1 diabetes during the COVID-19 pandemic in Kuwait - Al-Abdulrazzaq, Dalia; Khalifa, Doaa; Alqaisi, Taiba; Al-Juailla, Fatima; Othman, Fouzeyah; Qabazard, Sarah; Al-Kandari, Hessa (Frontiers in Public Health, 2022)
Background With the rapid transmission of COVID-19 globally, countries have implemented strict governmental measures and social distancing rules that aimed to minimize the spread of the virus. School closures, quarantine orders, and social isolation, coupled with a surge in family stress and lack of peer interactions, are probable causes of mental health complications and psychological symptoms faced by children. This study aims at comparing the HRQoL of children and adolescents with type 1 diabetes (T1D) and affected by COVID-19 infection (personal or familial) and those who were not affected by COVID-19. Materials and methods A random sample was selected from children and adolescents diagnosed with T1D at the six major governmental diabetes centers in Kuwait. To measure HRQoL, parent-proxy and self-reports from the Pediatric Quality of Life Inventory (PedsQLTM) 3.0 Diabetes Module were used. Results A sample of 455 children and adolescents with T1D diabetes (44.6% male participants and 41.98% affected by COVID-19 infection) was studied. The total score of the HRQoL self-reports was significantly higher compared with parent-proxy reports (79.06 ± 15.19 vs. 73.79 ± 15.17, p < 0.01). Children reported significantly higher HRQoL scores in the “treatment I” domain and “worry” domain and lower scores in the “diabetes” symptoms domain, compared with their parents' reports (p < 0.01). In the COVID-19-affected group, a major difference was noticed between the total scores of children and parent-proxy reports (77.04 ± 15.81 vs. 72.80±14.90, p = 0.047). The affected children reported significantly lower scores in “diabetes” symptoms (59.50) (p < 0.01) and higher scores in the “treatment I” domain (81.43) than their parent-proxy reports (72.05) (p < 0.01). Conclusion This is the first report on the health-related quality of life of children with T1D in Kuwait during the COVID-19 era. Parents' or caregivers' experience of caring for their children was negative, as they worried, and reported poorer HRQoL compared with their children's perceptions. There is a need to empower healthcare professionals to support parents and caregivers of children with chronic diseases such as T1D in promoting self-management, enhancing physical and psychological wellbeing, treatment adherence, and continuous health education during pandemics of any kind.